2006
DOI: 10.1007/bf02912905
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic analysis of secretory proteins ofAspergillus fumigatus with specific IGE immunoreactivity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…3wcf proteins were extracted from Afu (strain 285, isolated from the sputum of a patient with ABPA visiting Vallabhbhai Patel Chest Institute, Delhi, India) as described previously [23], for performing Afu ‐specific IgG ELISA, Afu ‐specific IgE ELISA, 2‐DE and 2‐D‐specific IgE immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3wcf proteins were extracted from Afu (strain 285, isolated from the sputum of a patient with ABPA visiting Vallabhbhai Patel Chest Institute, Delhi, India) as described previously [23], for performing Afu ‐specific IgG ELISA, Afu ‐specific IgE ELISA, 2‐DE and 2‐D‐specific IgE immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we had reported a comparative two‐dimensional gel electrophoresis (2‐DE) and immunoblot analysis of Afu culture filtrates (first‐, second‐ and third‐week culture filtrate) and third‐week culture filtrate (3wcf) showed a larger number of specific IgE immunoreactive proteins [23]. Hence, in the present study, 3wcf proteins of Afu were used to identify novel allergens using pooled sera of Afu ‐sensitized asthmatics and their allergenic potential was also studied in ABPA patients to establish the candidate allergens, which could be explored further for diagnostic applications in patients with allergic aspergillosis including ABPA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the clinical picture is generally accompanied with an elevated total IgE level and Aspergillus -specific elevated IgE and IgG levels [ 115 ]. Such anti- Aspergillus antibody profiles of ABPA patients (and of A. fumigatus sensitized asthmatics) have been analyzed in a number of immunoproteomic studies [ 116 119 ]. Gautam et al [ 116 ], for example, studied the IgE immunoreactivity of A. fumigatus proteins by 2D gel electrophoresis followed by immunoblotting of 3-week old culture filtrate proteins with sera from A. fumigatus -sensitized asthmatics and ABPA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Protease secretion is under the control of NCR mediated by the transcriptional regulator, PrtT, which was shown to not be essential for virulence when neutropenic and cortisone acetate-treated mice models of pulmonary aspergillosis (Bergmann et al ., 2009; Sharon et al ., 2009). Similar to C. albicans , proteases modulate host immune responses (Behnsen et al ., 2010) and are thought to contribute to A. fumigatus virulence by facilitating host tissue degradation and invasion (Gautam et al ., 2006; Balenga et al ., 2015; Kogan et al ., 2004). Deletion of the alkaline serine protease alp1/aspf13 led to significantly reduced virulence in nasally infected neutropenic mice (Kolatukuddy et al ., 1993), although a more recent study showed that disruption of alp1 had no significant effect on virulence, when the strain was administered intranasally, in a cortisone acetate mouse model (Behnsen et al ., 2010).…”
Section: Nitrogen Catabolite Metabolism In Human Pathogenic Fungimentioning
confidence: 99%